Effectiveness of Building Approval Services in the Department of Capital Investment and One-Door Integrated Services in Boyolali District Public Policy Law - Mukminati, Andan Hafsari; Maharani, Andina Elok Puri (International Journal of Sustainability in Research, 2024)
This research is intended to evaluate the effectiveness of building permit services at the Investment and Integrated One-Stop Service Office (DPMPTSP) of Boyolali Regency in order to improve public service to the community. The effectiveness of the Building Permit Service is a tool to measure the success of services at DPMPTSP in Boyolali, in accordance with applicable regulations. The building permit service at DPMPTSP of Boyolali Regency is carried out in accordance with the regulations stipulated in the Regent Regulation Number 4 of 2012 regarding Permit and Non-Permit Services. This research uses a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation, involving 8 informants. The effectiveness of the service is evaluated using the process approach according to Lubis and Huseini, which includes five indicators: service efficiency, procedures, employee responsiveness, coordination, and facilities and infrastructure. The results show that the building permit service at DPMPTSP of Boyolali Regency has not been maximized or effective, as evidenced by delays in processing permits, inadequate workspace infrastructure, lack of technical expertise, resulting in increased workload, and unclear building maintenance procedures.